2003
DOI: 10.1242/dev.00607
|View full text |Cite
|
Sign up to set email alerts
|

Two subunits of theDrosophilamediator complex act together to control cell affinity

Abstract: The organizing centers for Drosophila imaginal disc development are created at straight boundaries between compartments; these are maintained by differences in cell affinity controlled by selector genes and intercellular signals. skuld and kohtalo encode homologs of TRAP240 and TRAP230, the two largest subunits of the Drosophila mediator complex; mutations in either gene cause identical phenotypes. We show here that both genes are required to establish normal cell affinity differences at the anteriorposterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 87 publications
8
93
0
Order By: Relevance
“…These observations suggest that the mot͞med12 gene plays a regulatory role in vertebrate neuronal development. Consistent with this notion, it is interesting to mention that Caenorhabditis elegans (22)(23)(24)(25) and Drosophila (26,27) mutants in med12 also display specific phenotypes, and human polymorphisms in med12͞hopa correlate with distinct brain diseases such as schizophrenia and hypothyroidism (28).…”
Section: Discussionmentioning
confidence: 79%
“…These observations suggest that the mot͞med12 gene plays a regulatory role in vertebrate neuronal development. Consistent with this notion, it is interesting to mention that Caenorhabditis elegans (22)(23)(24)(25) and Drosophila (26,27) mutants in med12 also display specific phenotypes, and human polymorphisms in med12͞hopa correlate with distinct brain diseases such as schizophrenia and hypothyroidism (28).…”
Section: Discussionmentioning
confidence: 79%
“…Increasing evidence has shown that subunits in other topological positions participate in development regulation in a complex and precise manner. For instance, two subunits in the CDK module of the Drosophila Mediator, MED12 (TRAP230) and MED13 (TRAP240), physically interact with each other controlling cell affinity (Janody et al, 2003). In Arabidopsis, three subunits in the head module of the Mediator complex, MED17, MED18 and MED20, are involved in development by regulating the expression of micro-RNA biosynthesis genes .…”
Section: Discussionmentioning
confidence: 99%
“…17 mRNA expression of MED13L in human has been detected in fetal brain and heart, and adult tissues including skeletal muscle, brain (especially, cerebellum), heart and aorta, kidney and peripheral blood leukocytes. 2,3 Animal studies imply a specific role for MED13, similar in size and B50% identical to MED13L, in regulating transcription of Wnt and Notch target genes, and Hh signal transduction, [18][19][20] which are involved in neural crest induction. 21 Neural crest cell migration has an important role in the development of the heart, the nervous system and the facial mesenchyme, which could explain the syndromic signs of MED13L haploinsufficiency and the clinical overlap with DiGeorge Figure 2 Copy number variants of MED13L in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The third patient is a girl born 5 days preterm with a history of transient but marked fetal hydrops during pregnancy (weeks [16][17][18][19][20][21][22][23][24][25]. Her birth weight was 2200 g (o3rd centile) and the length was 47 cm (3rd centile).…”
Section: Patientmentioning
confidence: 99%